ANALISIS PENGARUH NET PROFIT MARGIN (NPM) DAN DEBT EQUITY RATIO (DER) TERHADAP RETURN OF STOCK PERUSAHAAN NON KEUANGAN DALAM LQ-45 DI BURSA EFEK INDONESIA (BEI) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2013)
This concept of financial performance is beginning to be explored is the net profit margin (NPM) and debt equity ratio (DER) affects the level of return of stock. Research methodology used in the journal companies whose shares are actively traded on the basis of trading frequency in Indonesia known as LQ-45 firms, but only 24 to non-financial companies in 2006 to 2008 in Indonesian stock exchange. This research using the model of multiple regression statistical analysis to determine the effects of independent variables on the dependent variable and the assumption of classical test equipment to see if there are irregularities in the assumption of classical test. The result of the research showed that NPM and DER have a significant impact either partially or in conjunction with the level of return of stock and not the classical assumption deviation occurs after passing the autokorelasi, heterokedastisitas, multikolinearitas and normality tests.